The use of the structural units for the description of the short-range order in the amorphous substances - Valentyn Ivanitsky; Victor Kovtunenko; Myhajlo Ryaboschuk; Stoika Myroslav; Sztojka Miroszláv; Валентин Іваницький; Віктор Ковтуненко; Михайло Рябощук; Стойка Мирослав (Society for Cultural and Scientific Progress in Central and Eastern Europe, 2016)
Abstract. It is proposed to define the structure of the amorphous substance by the set of all realized structural units with the allowance made for the functions of their statistical distribution in the disordered atomic network. In the aggregate, all these elements make basis for constructing the minimal elementary structural fragment of the amorphous substance – an analog of the elementary cell in the crystal. Solution of this task is reduced to the correct choice of structural units and determination of their structural parameters. In this relation, the partitioning of the sample that expresses its structural and chemical composition using the minimal number of different-kind structural units seems to be optimal.
Keywords: amorphous materials; disorder structure; short range order; structural unit; amorf anyagok; rendellenesség szerkezete; rövid hatótávolságú sorrend; szerkezeti egység; аморфні матеріали; невпорядкована структура; ближній порядок; структурна одиниця